Normalizing Plagiarism: An Analysis of Copy-Paste Culture and the Shifting Values of Academic Honesty in the Era of Artificial Intelligence (AI) - I Wayan Gama (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to explore the shift in students' ethical paradigms regarding the use of Generative Artificial Intelligence (AI) and its relationship to the phenomenon of plagiarism. Using a qualitative approach with the theoretical frameworks of Jean Baudrillard's Simulacra and Pierre Bourdieu's Habitus, this study examines how AI technology is changing the nature of scientific work. The results show the normalization of AI use as a new